Waterproof carbon brush for wind turbine and its manufacturing method

By designing the engagement structure and protective layer of the waterproof phase carbon brush in the wind turbine, the wear and chemical reaction problems of the carbon brush during high-speed operation are solved, extending the service life and reducing operating losses.

CN112217072BActive Publication Date: 2024-12-20MAIJIA CARBON PROD (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202011094104.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-10-14
Publication Date
2024-12-20
Estimated Expiration
2040-10-14

AI Technical Summary

Technical Problem

When the wind turbine runs at high speed, the carbon brushes wear, increase impedance, poor contact, and powdered particles fall off, resulting in a decrease in resistance and life. The direct contact between the carbon brushes and water and salt causes chemical reactions, which are charged and ignited, overheating, and swelling. Brush hold.

Method used

A waterproof phase carbon brush of the wind turbine is designed, using the engagement structure between the carbon brush body and the sleeve, combining the elastic parts and flexible rods to form a special-shaped hole structure, avoiding the contact between the carbon brush and the inner wall of the sleeve, and adding protective layer to resist Cut off water and salt to increase the strength of the carbon brush and flexural strength, and adjust the contact state through the conductor.

Benefits of technology

It effectively avoids ablation and jamming of carbon brushes, extends the service life of the carbon brush, reduces losses and economic costs during the operation of the wind turbine, and improves the wear resistance and conductivity of the carbon brushes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112217072B_ABST
    Figure CN112217072B_ABST
Patent Text Reader

Abstract

The invention relates to the wind power industry of new clean energy, and is specifically applied to double-fed wind power generator sets of different powers, and more specifically to a waterproof phase carbon brush of a wind power generator set, comprising a carbon brush body and a sleeve, wherein the sleeve is provided with an axial hole from the bottom end upward, and the carbon brush body is installed in the axial hole through a clamping structure, and the clamping structure comprises a hinged part, a hinged part and a clamping base. A manufacturing method of the waterproof phase carbon brush of the wind power generator set is also provided, comprising the following steps: S1, material preparation, the carbon brush body comprises at least one functional layer and one protective layer, the functional layer comprises a carbon matrix, and the carbon matrix comprises carbon graphite, tin powder, lead powder, copper powder and asphalt binder; S2, uniformly mixing powdery materials required for making the carbon matrix, and performing molding treatment; S3, heating and boiling aluminum soap and black engine oil of a saponified liquid to obtain liquid A, etc., and providing a manufacturing method that can enhance the strength and flexural strength of the carbon brush body and extend the service life of the carbon brush.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wind power industry of new clean energy, and in particular to a waterproof phase carbon brush of a wind turbine set and a manufacturing method thereof. Background Art

[0002] As the units developed become larger and larger, the application environment becomes worse, the requirements become higher, and the differences in seasonal changes become more obvious. The developed wind farms are moving from inland to plateaus, to tidal zones, to offshore, and to the deep blue. Therefore, the traditional carbon brushes cannot meet the requirements of the new environment and new technical standards, and users have higher expectations. To this end, we must take advantage of market demand and actively develop new carbon materials that are suitable for wind turbines in high humidity and high salt environments, so that the carbon brushes have certain waterproof, moisture-proof and salt-resistant properties, reduce the maintenance of wind turbine slip rings and carbon brushes, and have a longer lifespan, and are not prone to thermal expansion and jamming.

[0003] For graphite brushes, a carbon protective film is formed on the sliding contact surface with the help of air around the sliding contact part of the commutator and air in the pores inside the brush. This carbon protective film becomes a factor in suppressing wear and deterioration of rectification performance. However, it is known that the formation state of the aforementioned carbon protective film is strongly affected by the use environment at the sliding contact part of the brush and the commutator, that is, temperature and humidity. When the atmospheric temperature of the sliding contact part becomes high temperature, there is a problem that the formation of a proper carbon protective film is damaged, the sliding contact state between the brush and the commutator is deteriorated, the occurrence of sparks increases, and the durability is deteriorated.

[0004] The Chinese patent with publication number CN201820155720.9 discloses a generator carbon brush that can reduce carbon brush sparks, which belongs to the technical field of excitation generator equipment and is used to reduce carbon brush sparks. Its technical solution is: a plurality of parallel grooves are opened on the surface of the carbon brush, the grooves are perpendicular to the surface of the carbon brush, the direction of the grooves on the surface is perpendicular to the length direction of the surface, and the plurality of grooves divide the surface of the carbon brush into a plurality of grids. After the carbon brush surface of the utility model is provided with grooves, the total contact area of ​​the carbon brush surface is composed of a plurality of small areas, which is easy to contact better during operation, thereby reducing the sparks; if sparks are generated, the sparks will be rapidly reduced in the gaps between adjacent grooves, and splashing is not easy to occur, thereby reducing the spark level. The patent has a simple structure, can reduce the carbon brush sparks, and significantly reduces the carbon brush spark level, thereby reducing the heating of the carbon brush and the slip ring, avoiding burning, ensuring the stable operation of the generator, and increasing the reactive power of the generator.

[0005] The Chinese patent with publication number CN102013609B discloses a sealed carbon brush and its manufacturing and use methods. The sealed carbon brush includes a housing, a cylindrical brush block, and an oil seal frame; the characteristic is that a guide sleeve is arranged in the housing, one section of the cylindrical brush block passes through the housing until it reaches the inside of the guide sleeve, and the other section is exposed outside the housing; an oil seal frame is arranged at one end of the guide sleeve, and a guide sleeve rear cover is arranged at the other end, and one end of the oil seal frame passes through the housing and is threadedly connected to the guide sleeve. The advantages of this invention are simple structure, easy use, good sealing, corrosion resistance, and can maintain good electrical connection in seawater splashing and humid environment.

[0006] However, the above patents still have the following problems:

[0007] When the fan is running at high speed, the return carbon brush wear, the impedance of the carbon brush itself, and the poor contact of the carbon brush lead to poor contact;

[0008] When the fan is running at high speed, the powder particles are easy to fall off due to friction and vibration, which reduces the durability and life of the carbon brush;

[0009] When the fan is running at high speed, the carbon brush comes into direct contact with salt and water, which will cause a direct chemical reaction between the carbon brush, water and salt, sparking the carbon brush, and overheating and expanding, thus preventing the carbon brush from getting stuck in the brush holder. Summary of the invention

[0010] The present invention aims at the above problems existing in the prior art. The present invention provides a wind turbine waterproof phase carbon brush, which has a waterproof function compared to the prior art carbon brush assembly, blocks direct contact between water and salt and the brush body, avoids the carbon brush from sparking when it is electrified, avoids overheating and expansion of the carbon brush, and also avoids the occurrence of the carbon brush stuck in the brush holder. It also provides a method for manufacturing a wind turbine waterproof phase carbon brush, which can enhance the strength and flexural strength of the carbon brush body, and ensure the stable formation of the oxide film on the surface of the carbon brush body, thereby extending the service life of the carbon brush.

[0011] The basic scheme of the present invention is: a wind turbine waterproof phase carbon brush, comprising a carbon brush body and a sleeve, wherein the sleeve is provided with an axial hole from the bottom end upward, wherein the axial hole is a special-shaped hole, wherein the carbon brush body is installed in the axial hole through a clamping structure, and the carbon brush body does not contact the inner wall of the axial hole, wherein the clamping structure comprises a hinged part, a second hinged part and a clamping base, wherein the diameter of the clamping base is greater than the diameter of the bottom of the axial hole, wherein the second hinged part is installed above the clamping base, wherein the first hinged part is installed below the carbon brush body, wherein the bottom of the first hinged part and the top of the second hinged part are hinged, wherein an elastic member is connected below the clamping base, wherein a flexible rod is sleeved inside the elastic member, wherein the bottom of the elastic member and the flexible rod are connected to a mounting base through a buffer rod;

[0012] The top of the carbon brush body is connected with a conductive part, and the conductive part is arranged outside the sleeve.

[0013] Preferably, a right-angle groove is opened on the top of the sleeve, and the right-angle groove is connected with the sleeve, and the conductive part includes a conductive part one, a conductive line and a conductive part two, the conductive part one is arranged in the right-angle groove, and one end of the conductive part one is hinged to the inner wall of the right-angle groove, the other end of the conductive part one is connected to the conductive part two through the conductive line, and the carbon brush transmits the signal to the conductive part two through the conductive part one and the conductive line, and a wiring piece is connected to the top of the conductive part two, and the wiring piece is a conductor.

[0014] Preferably, the carbon brush body includes a functional layer and a protective layer, the functional layer includes a carbon matrix, the carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and a non-shrinking mixed binder, and in terms of weight ratio, the carbon graphite accounts for 35%-45% of each carbon matrix, the tin powder accounts for 0.3%-0.5%, the lead powder accounts for 6%-8%, the copper powder accounts for 45%-50%, and the non-shrinking mixed binder accounts for 3%-5%.

[0015] Preferably, the carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and asphalt binder. According to the weight ratio, the carbon graphite accounts for 39% of each carbon matrix, the tin powder accounts for 0.4%, the lead powder accounts for 7%, the copper powder accounts for 48%, and the non-shrinkage mixed binder accounts for 5.6%.

[0016] Preferably, the purity of the tin powder is 99.5%-99.8%, the purity of the lead powder is 99.4%-99.7%, and the purity of the copper powder is 99.4%-99.6%.

[0017] Preferably, the purity of the tin powder is 99.7%, the purity of the lead powder is 99.6%, and the purity of the copper powder is 99.5%.

[0018] Preferably, the non-shrinkage mixed binder is a mixture of an asphalt binder and a resin binder, and the mixing ratio of the asphalt binder to the resin binder is (0.3-0.5):1.

[0019] Preferably, the protective layer is a composite saponified liquid, the composite saponified liquid includes aluminum soap and black engine oil, and the ratio of the aluminum soap to the black engine oil is 10:90.

[0020] The present invention also provides a method for manufacturing a waterproof phase carbon brush for a wind turbine generator set, comprising the following steps:

[0021] S1. Material preparation. The carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and asphalt binder. According to the weight ratio, the carbon graphite accounts for 39% of each carbon matrix, the tin powder accounts for 0.4%, the lead powder accounts for 7%, the copper powder accounts for 48%, and the non-shrinkage mixed binder accounts for 5.6%. The purity of the tin powder is 99.7%, the purity of the lead powder is 99.6%, and the purity of the copper powder is 99.5%. The composite saponification liquid includes aluminum soap and black engine oil, and the ratio of the aluminum soap to the black engine oil is 10:90. Prepare the carbon matrix material and the composite saponification liquid material according to the following ratios and purity requirements;

[0022] S2, crushing the powdery materials required for making the carbon matrix, placing the materials required for the carbon matrix in a water-free and oil-free glass container, mixing them evenly by kneading, and then stirring them evenly by a stirrer, and sending the stirred mixed materials for pressing;

[0023] S3, performing molding treatment, molding the mixed material after stirring for three times, with the interval between each molding not exceeding 5 minutes, the temperature of the first molding is 0°C, the temperature of the second molding is 450-550°C, and the temperature of the third molding is 750-850°C;

[0024] S4, the molding material after three moldings enters high temperature sintering, and the temperature of high temperature sintering is controlled at 900-950 degrees Celsius;

[0025] S5, placing the high-temperature sintered carbon substrate in an oven at 980° C. for no more than 5 hours;

[0026] S6, placing the carbon substrate treated in S5 in a composite saponification solution for immersion treatment for at least 12 hours;

[0027] S7, taking out the carbon matrix after the impregnation treatment and placing it at 250° C.-270° C. for high-temperature curing for no more than 6 hours, and then taking it out of the furnace to obtain a carbon brush body.

[0028] Preferably, the preparation process of the composite saponified liquid comprises the following steps:

[0029] Step 1: Aluminum soap and black engine oil in a mass ratio of 10:90 are boiled at 300 degrees Celsius for at least 5 hours to obtain product A, and the product A is white and sticky;

[0030] Step 2: Add the boiled A into gasoline for dilution to obtain a composite saponified liquid, and the gasoline is No. 95 gasoline, and the mixing ratio of gasoline and product A is 1:1.

[0031] Compared with the prior art, the working principle and advantages of the present invention are:

[0032] The carbon brush body is installed in the axial hole of the sleeve, and when the carbon brush body is placed in a waiting state, the elastic member is in a compressed state, and there is a gap between the upper surface of the carbon brush body and the top of the axial hole. When the carbon brush body is placed in a working state, the elastic member is in a natural state, and the upper surface of the carbon brush body contacts the top of the axial hole. The elastic member returns to the natural state from the compressed state, and in this process, the elastic member and the carbon brush body rotate synchronously, and the carbon brush body enters the working state under rotation. At this time, the electrical signal is transmitted through the conductive member at the top of the sleeve, and a snap-fit ​​structure is connected to the bottom of the carbon brush body. The snap-fit ​​structure includes a hinged part, a hinged part and a snap-fit ​​base. The carbon brush may expand under long-term work, but when it is still within the acceptable expansion range, the carbon brush can still be used normally. However, in conventional designs, when a part of the carbon brush expands, the carbon brush will contact and be held against the inner wall of the sleeve, causing the carbon brush to be unable to continue to rotate. By using the snap-fit ​​structure, the carbon brush can automatically adjust the internal position to work normally.

[0033] A right-angle groove is installed on the top of the sleeve, and the conductive part 1 is installed in the right-angle groove. The conductive part is movably connected to the right-angle groove. When the carbon brush body enters the working state, the elastic part is in a natural state, and the upper surface of the carbon brush body contacts the top of the axial hole. At this time, the top of the carbon brush body will push out the conductive part 1, so that the position of the conductive part 1 and the conductive part 2 can be adjusted, which is convenient for connection with external parts.

[0034] The waterproof carbon brush for wind turbines obtained by the above manufacturing method can avoid repeated carbon brush and slip ring ablation, avoid affecting the operation of the wind turbine, and reduce attack losses. Tin powder, lead powder, copper powder and asphalt adhesive are added to the material of the carbon matrix, thereby improving the strength, flexural strength, surface smoothness, wear resistance and conductivity of the carbon brush, adding external current to the rotating rotor through the carbon brush, and introducing the static charge on the main shaft into the ground through the carbon brush. The carbon brush body in the manufacturing process is impregnated, and a protective layer is added to the carbon brush body. The protective layer is similar to a protective film attached to the carbon brush body, which blocks water and salt from directly contacting the carbon brush body, thereby avoiding direct chemical reactions between the carbon brush and water and salt when the wind turbine is in operation, causing the carbon brush to be charged and ignited, and the carbon brush to overheat and expand, thereby avoiding the occurrence of carbon brush jamming and brush grip, and avoiding repeated carbon brush and slip ring ablation, affecting the operation and power generation of the unit, and causing huge economic losses to the owner. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a three-dimensional structural diagram of an embodiment of a waterproof carbon brush for a wind turbine according to the present invention;

[0036] Figure 2 It is a cross-sectional view of a waterproof carbon brush for a wind turbine generator set of the present invention;

[0037] Figure 3 This is a metallographic image of the copper powder used in the production process of the wind turbine waterproof carbon brush of the present invention at a magnification of 2K;

[0038] Figure 4 This is a metallographic image of the copper powder used in the production process of the wind turbine waterproof carbon brush of the present invention at a magnification of 5K;

[0039] Figure 5 It is a line diagram showing the change of voltage drop when the waterproof phase carbon brush of the wind turbine of the present invention is working;

[0040] Figure 6 This is a line diagram showing the change in the friction coefficient of the waterproof carbon brush of the wind turbine set of the present invention when it is working.

[0041] The reference numerals involved in the accompanying drawings are: carbon brush body 1, contact end 101, hinged part 102, hinged part 2 103, snap-fit ​​base 104, mounting base 2, buffer rod 3, elastic member 4, flexible rod 401, protective shell 5, sleeve 6, right-angle groove 601, conductive part 1 801, conductive line 802, conductive part 2 803, slider 803a, slide rail 803b. DETAILED DESCRIPTION

[0042] The following is a further detailed description through specific implementation methods: Example

[0043] like Figure 1-2 As shown, the wind turbine waterproof phase carbon brush comprises a carbon brush body 1 and a sleeve 6. The sleeve 6 has an axial hole from the bottom end upward, and the axial hole is a special-shaped hole. The carbon brush body 1 is installed in the axial hole through a clamping structure, and the carbon brush body 1 does not contact the inner wall of the axial hole. The clamping structure comprises a hinged part 102, a second hinged part 103 and a clamping base 104. The diameter of the clamping base 104 is larger than the bottom diameter of the axial hole. The second hinged part 103 is installed above the clamping base 104. The hinged part 102 is installed below the carbon brush body 1, the bottom of the hinged part 102 and the top of the hinged part 103 are hinged, and an elastic member 4 is connected to the bottom of the snap-fit ​​base 104, an axially penetrating protective shell 5 is installed at the bottom of the sleeve 6, the elastic member 4 is installed in the protective shell 5, and a flexible rod 401 is sleeved in the elastic member 4, the bottom of the elastic member 4 and the flexible rod 401 are connected to the mounting base 2 through the buffer rod 3, and a conductive member is connected to the top of the carbon brush body 1, and the conductive member is arranged outside the sleeve 6.

[0044] Preferably, a right-angle groove 601 is opened on the top of the sleeve 6, and the right-angle groove 601 is connected with the sleeve 6, and the conductive part includes a conductive part 801, a conductive line 802 and a conductive part 2 803. The conductive part 801 is arranged in the right-angle groove 601, and one end of the conductive part 801 is hinged to the inner wall of the right-angle groove 601, and the other end of the conductive part 801 is connected to the conductive part 2 803 through the conductive line 802, and a contact end 101 is provided on the top of the carbon brush, and the contact end 101 transmits the signal to the conductive part 2 803 through the conductive part 1 801 and the conductive line 802, and a wiring piece is connected to the top of the conductive part 803, which is a conductor.

[0045] The outer surfaces of the first conductive part 801, the conductive wire 802 and the second conductive part 803 are all provided with an insulating layer. One end of the second conductive part 803 is connected to the conductive wire 802, and the other end of the second conductive part 803 is provided with a receiving groove, and the terminal piece is provided in the receiving groove. A slide rail 803b is provided on the side of the second conductive part 803, and a slider 803a is slidably connected in the slide rail 803b. The slider 803a is H-shaped, and one end of the slider 803a is installed inside the slide rail 803b and fixedly connected to the top of the terminal piece, and the other end of the slider 803a is installed outside the slide rail 803b. When the slider 803a is placed on the top of the slide rail 803b, the terminal piece is completely placed in the receiving groove. When the slider 803a moves to the bottom of the slide rail 803b, the terminal piece moves outside the receiving groove. The position of the terminal block is adjusted by the slider 803a. When in an idle state, the slider 803a is at the top of the slide rail 803b. When work is required, the slider 803a is slid to the bottom of the slide rail 803b to expose the terminal block, thereby connecting external parts. Since the structure of the terminal block is small and mostly made of thin metal sheets, it is easy to be damaged. Such a structure can be used to protect the terminal block and prevent it from wear.

[0046] As a preferred embodiment, the carbon brush body 1 includes a functional layer and a protective layer, the functional layer includes a carbon matrix, the carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and a non-shrinking mixed binder, and according to the weight ratio, the carbon graphite accounts for 35%-45% of each carbon matrix, the tin powder accounts for 0.3%-0.5%, the lead powder accounts for 6%-8%, the copper powder accounts for 45%-50%, and the non-shrinking mixed binder accounts for 3%-5%.

[0047] As a preferred solution, the purity of the tin powder is 99.5%-99.8%, the purity of the lead powder is 99.4%-99.7%, and the purity of the copper powder is 99.4%-99.6%.

[0048] As a preferred solution, the protective layer is a composite saponified liquid, which includes aluminum soap and black engine oil, and the ratio of the aluminum soap to the black engine oil is 10:90.

[0049] The carbon brush body 1 is installed in the axial hole of the sleeve 6, and when the carbon brush body 1 is placed in the waiting state, the elastic member 4 is in a compressed state, and there is a gap between the upper surface of the carbon brush body 1 and the top of the axial hole. When the carbon brush body 1 is placed in the working state, the elastic member 4 is in a natural state, and the upper surface of the carbon brush body 1 contacts the top of the axial hole. The elastic member 4 returns to the natural state from the compressed state, and in this process, the elastic member 4 and the carbon brush body 1 rotate synchronously, and the carbon brush body 1 enters the working state under rotation. At this time, the transmission at the top of the sleeve 6 The guide transmits electrical signals, and a snap-fit ​​structure is connected to the bottom of the carbon brush body 1, which includes a hinged portion 102, a hinged portion 103 and a snap-fit ​​base 104. The carbon brush may expand under long-term work, but when it is still within the acceptable expansion range, the carbon brush body can still be used normally. However, in conventional designs, when a certain part of the carbon brush body 1 expands, the carbon brush body 1 will contact and be resisted by the inner wall of the sleeve 6, causing the carbon brush body 1 to be unable to continue to rotate. By using the snap-fit ​​structure, the carbon brush body 1 can automatically adjust the internal position to work normally.

[0050] A right-angle groove 601 is installed on the top of the sleeve 6, and the first conductive part 801 is installed in the right-angle groove 601. The conductive part is movably connected to the right-angle groove 601. When the carbon brush body 1 enters the working state, the elastic member 4 is in a natural state, and the upper surface of the carbon brush body 1 contacts the top of the axial hole. At this time, the top of the carbon brush body 1 pushes out the first conductive part 801, so that the positions of the first conductive part 801 and the second conductive part 803 can be adjusted, which is convenient for connection with external parts.

[0051] The waterproof carbon brush for wind turbines obtained by the above manufacturing method can avoid repeated carbon brush and slip ring ablation, avoid affecting the operation of the wind turbine, and reduce attack losses. Tin powder, lead powder, copper powder and asphalt adhesive are added to the material of the carbon matrix, thereby improving the strength, flexural strength, surface smoothness, wear resistance and conductivity of the carbon brush. The external current is added to the rotating rotor through the carbon brush body 1, and the static charge on the main shaft is introduced into the ground through the carbon brush. The carbon brush body 1 in the manufacturing process is impregnated, and a protective layer is added to the carbon brush body 1. The protective layer is similar to a protective film attached to the carbon brush body, which blocks water and salt from directly contacting the carbon brush body, thereby avoiding direct chemical reactions between the carbon brush and water and salt when the wind turbine is in operation, causing the carbon brush to be charged and ignited, and the carbon brush to overheat and expand, thereby avoiding the occurrence of carbon brush jamming and brush grip, and avoiding repeated carbon brush and slip ring ablation, affecting the operation and power generation of the unit, and causing huge economic losses to the owner. Example

[0052] like Figure 1-2 As shown, Figure 1-2As shown, the wind turbine waterproof phase carbon brush includes a carbon brush body 1 and a sleeve 6. The sleeve 6 has an axial hole from the bottom end to the top, and the axial hole is a special-shaped hole. The carbon brush body 1 is installed in the axial hole through a clamping structure, and the carbon brush body 1 does not contact the inner wall of the axial hole. The clamping structure includes a hinged part 102, a second hinged part 103 and a clamping base 104. The diameter of the clamping base 104 is larger than the bottom diameter of the axial hole. The second hinged part 103 is installed above the clamping base 104, and the first hinged part 102 is installed below the carbon brush body 1. The bottom of the first hinged part 102 and the top of the second hinged part 103 are hinged, and an elastic member 4 is connected below the clamping base 104, and a flexible rod 401 is sleeved in the elastic member 4. The bottom of the elastic member 4 and the flexible rod 401 are connected to the mounting base 2 through a buffer rod 3. The top of the carbon brush body 1 is connected to a conductive member, and the conductive member is arranged outside the sleeve 6.

[0053] Preferably, a right-angle groove 601 is opened on the top of the sleeve 6, and the right-angle groove 601 is connected with the sleeve 6, and the conductive part includes a conductive part 801, a conductive line 802 and a conductive part 2 803. The conductive part 801 is arranged in the right-angle groove 601, and one end of the conductive part 801 is hinged to the inner wall of the right-angle groove 601, and the other end of the conductive part is connected to the conductive part 2 803 through the conductive line 802, and the carbon brush transmits the signal to the conductive part 2 803 through the conductive part 1 801 and the conductive line 802. The top of the conductive part 2 803 is connected with a wiring piece, which is a conductor.

[0054] The outer surfaces of the first conductive part 801, the conductive wire 802 and the second conductive part 803 are all provided with an insulating layer. One end of the second conductive part 803 is connected to the conductive wire 802, and the other end of the second conductive part 803 is provided with a receiving groove, and the terminal piece is provided in the receiving groove. A slide rail 803b is provided on the side of the second conductive part 803, and a slider 803a is slidably connected in the slide rail 803b. The slider 803a is H-shaped, and one end of the slider 803a is installed inside the slide rail 803b and fixedly connected to the top of the terminal piece, and the other end of the slider 803a is installed outside the slide rail 803b. When the slider 803a is placed on the top of the slide rail 803b, the terminal piece is completely placed in the receiving groove. When the slider 803a moves to the bottom of the slide rail 803b, the terminal piece moves outside the receiving groove. The position of the terminal block is adjusted by the slider 803a. When in an idle state, the slider 803a is at the top of the slide rail 803b. When work is required, the slider 803a is slid to the bottom of the slide rail 803b to expose the terminal block, thereby connecting external parts. Since the structure of the terminal block is small and mostly made of thin metal sheets, it is easy to be damaged. Such a structure can be used to protect the terminal block and prevent it from wear.

[0055] The carbon brush body 1 includes a functional layer and a protective layer, the functional layer includes a carbon matrix, the carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and a non-shrinkage mixed binder, and by weight, the carbon graphite accounts for 39% of each carbon matrix, the tin powder accounts for 0.4%, the lead powder accounts for 7%, the copper powder accounts for 48%, and the non-shrinkage mixed binder accounts for 5.6%.

[0056] As a preferred solution, the purity of tin powder is 99.7%, the purity of lead powder is 99.6%, and the purity of copper powder is 99.5%. The metallographic diagram of the selected copper powder is as follows: Figure 3 and 4 shown.

[0057] As a preferred solution, the non-shrinkage mixed binder is a mixture of an asphalt binder and a resin binder, and the mixing ratio of the asphalt binder to the resin binder is (0.3-0.5):1.

[0058] As a preferred solution, the protective layer is a composite saponified liquid, which includes aluminum soap and black engine oil, and the ratio of the aluminum soap to the black engine oil is 10:90.

[0059] The advantages of Example 2 over Example 1 are: after repeated experiments, the proportion of carbon graphite is 39%, the proportion of tin powder is 0.4%, the proportion of lead powder is 7%, the proportion of copper powder is 48%, the proportion of non-shrinkage mixed binder is 5.6%, the purity of tin powder is 99.7%, the purity of lead powder is 99.6%, the purity of copper powder is 99.5%, the non-shrinkage mixed binder is a mixture of asphalt binder and resin binder, and the mixing ratio of asphalt binder and resin binder is (0.3-0.5): 1. The hardness and flexural strength of the carbon brush body 1 produced under this requirement are optimal, and the oxide film formed on the surface of the carbon brush is more stable and not easy to be destroyed, thereby improving the service life of the carbon brush. In addition, asphalt binder and resin binder, asphalt binder is used as aggregate of carbon material, and the aggregate hardly shrinks during the roasting process of carbon block material, and the volume fraction of asphalt binder is relatively small, so it is not easy to crack during roasting.

[0060] The present invention also provides a method for manufacturing a waterproof phase carbon brush for a wind turbine generator set, comprising the following steps:

[0061] S1. Material preparation. The carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and asphalt binder. According to the weight ratio, the proportion of carbon graphite in each carbon matrix is ​​39%, the proportion of tin powder is 0.4%, the proportion of lead powder is 7%, the proportion of copper powder is 48%, the proportion of non-shrinkage mixed binder is 5.6%, the purity of tin powder is 99.7%, the purity of lead powder is 99.6%, and the purity of copper powder is 99.5%. The composite saponification liquid includes aluminum soap and black engine oil, and the ratio of aluminum soap to black engine oil is 10:90. Prepare the carbon matrix material and composite saponification liquid material according to the following ratios and purity requirements;

[0062] S2, crushing the powdery materials required for making the carbon matrix, placing the materials required for the carbon matrix in a water-free and oil-free glass container, mixing them evenly by kneading, and then stirring them evenly by a stirrer, and sending the stirred mixed materials for pressing;

[0063] S3, performing molding treatment, molding the mixed material after stirring for three times, with the interval between each molding not exceeding 5 minutes, the temperature of the first molding is 0°C, the temperature of the second molding is 450-550°C, and the temperature of the third molding is 750-850°C;

[0064] S4, the molding material after three moldings enters high temperature sintering, and the temperature of high temperature sintering is controlled at 900-950 degrees Celsius;

[0065] S5, placing the high-temperature sintered carbon substrate in an oven at 980° C. for no more than 5 hours;

[0066] S6, placing the carbon substrate treated in S5 in a composite saponification solution for immersion treatment for at least 12 hours;

[0067] S7, taking out the carbon matrix after the impregnation treatment and placing it at 250° C.-270° C. for high-temperature curing for no more than 6 hours, and then taking it out of the furnace to obtain the carbon brush body 1.

[0068] As a preferred embodiment, the preparation process of the composite saponified liquid includes the following steps:

[0069] Step 1: Aluminum soap and black engine oil in a mass ratio of 10:90 are boiled at 300 degrees Celsius for at least 5 hours to obtain product A, and the product A is white and sticky;

[0070] Step 2: Add the boiled A into gasoline for dilution to obtain a composite saponified liquid, and the gasoline is No. 95 gasoline, and the mixing ratio of gasoline and product A is 1:1.

[0071] Take two carbon brushes obtained by the above method for dynamic test. When the carrying current is 5A / cm2, the voltage drop of the two carbon brushes is below 0.5V. When the carbon brush carries the current to 15A / cm2, the voltage drop of the two carbon brushes is below 1.0V. The voltage drop change line diagram between the two carbon brushes at a linear speed of 40m / s is as follows Figure 5 As shown, the friction coefficient of two carbon brushes working at 25A / cm2 is as follows Figure 6 shown.

[0072] The above is only an embodiment of the present invention. The common sense such as the known specific structure and characteristics in the scheme is not described in detail here. The ordinary technicians in the relevant field are aware of all the common technical knowledge in the technical field of the invention before the application date or priority date, can obtain all the existing technologies in the field, and have the ability to apply the conventional experimental means before that date. The ordinary technicians in the relevant field can improve and implement the scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for the ordinary technicians in the relevant field to implement this application. It should be pointed out that for the technicians in this field, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. Waterproof carbon brush for wind turbine, characterized by: It comprises a carbon brush body and a sleeve, wherein the sleeve is provided with an axial hole from the bottom end upward, wherein the axial hole is a special-shaped hole, wherein the carbon brush body is installed in the axial hole through a clamping structure, and the carbon brush body does not contact the inner wall of the axial hole, wherein the clamping structure comprises a hinged part, a second hinged part and a clamping base, wherein the diameter of the clamping base is greater than the diameter of the bottom of the axial hole, wherein the second hinged part is installed above the clamping base, wherein the first hinged part is installed below the carbon brush body, wherein the bottom of the first hinged part and the top of the second hinged part are hinged, wherein an elastic member is connected below the clamping base, wherein a flexible rod is sleeved inside the elastic member, wherein the bottom of the elastic member and the flexible rod are connected to a mounting base through a buffer rod; The top of the carbon brush body is connected with a conductive part, and the conductive part is arranged outside the sleeve.

2. The wind turbine waterproof carbon brush according to claim 1, characterized in that: A right-angle groove is opened on the top of the sleeve, and the right-angle groove is connected with the sleeve through, the conductive part includes a conductive part one, a conductive line and a conductive part two, the conductive part one is arranged in the right-angle groove, and one end of the conductive part one is hinged to the inner wall of the right-angle groove, the other end of the conductive part one is connected to the conductive part two through the conductive line, and the carbon brush transmits the signal to the conductive part two through the conductive part one and the conductive line, and a wiring piece is connected to the top of the conductive part two, and the wiring piece is a conductor.

3. The wind turbine waterproof carbon brush according to claim 1 or 2, characterized in that: The carbon brush body includes a functional layer and a protective layer, the functional layer includes a carbon matrix, and the carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and a non-shrinkage mixed binder. According to the weight ratio, the carbon graphite accounts for 35%-45% of each carbon matrix, the tin powder accounts for 0.3%-0.5%, the lead powder accounts for 6%-8%, the copper powder accounts for 45%-50%, and the non-shrinkage mixed binder accounts for 3%-5%.

4. The wind turbine waterproof phase carbon brush according to claim 3 is characterized in that: The carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and asphalt binder. According to weight ratio, carbon graphite accounts for 39% of each carbon matrix, tin powder accounts for 0.4%, lead powder accounts for 7%, copper powder accounts for 48%, and non-shrinkage mixed binder accounts for 5.6%.

5. The wind turbine waterproof phase carbon brush according to claim 4, characterized in that: The purity of the tin powder is 99.5%-99.8%, the purity of the lead powder is 99.4%-99.7%, and the purity of the copper powder is 99.4%-99.6%.

6. The wind turbine waterproof phase carbon brush according to claim 5, characterized in that: The purity of the tin powder is 99.7%, the purity of the lead powder is 99.6%, and the purity of the copper powder is 99.5%.

7. The wind turbine waterproof phase carbon brush according to claim 6, characterized in that: The non-shrinkage mixed binder is a mixture of an asphalt binder and a resin binder, and the mixing ratio of the asphalt binder to the resin binder is (0.3-0.5):

1.

8. The wind turbine waterproof phase carbon brush according to claim 7, characterized in that: The protective layer is a composite saponified liquid, which includes aluminum soap and black engine oil, and the ratio of the aluminum soap to the black engine oil is 10:

90.

9. The method for manufacturing a waterproof carbon brush for a wind turbine according to claim 8, characterized in that: The following steps are involved: S1. Material preparation. The carbon matrix includes carbon graphite, tin powder, lead powder, copper powder and asphalt binder. According to the weight ratio, the carbon graphite accounts for 39% of each carbon matrix, the tin powder accounts for 0.4%, the lead powder accounts for 7%, the copper powder accounts for 48%, and the non-shrinkage mixed binder accounts for 5.6%. The purity of the tin powder is 99.7%, the purity of the lead powder is 99.6%, and the purity of the copper powder is 99.5%. The composite saponification liquid includes aluminum soap and black engine oil, and the ratio of the aluminum soap to the black engine oil is 10:

90. Prepare the carbon matrix material and the composite saponification liquid material according to the following ratios and purity requirements; S2, crushing the powdery materials required for making the carbon matrix, placing the materials required for the carbon matrix in a water-free and oil-free glass container, mixing them evenly by kneading, stirring them evenly by a stirrer, and pressing the stirred mixed materials; S3, performing molding treatment, molding the mixed material after stirring for three times, with the interval between each molding not exceeding 5 minutes, the temperature of the first molding is 0°C, the temperature of the second molding is 450-550°C, and the temperature of the third molding is 750-850°C; S4, the molding material after three moldings enters high temperature sintering, and the temperature of high temperature sintering is controlled at 900-950 degrees Celsius; S5, placing the high-temperature sintered carbon matrix in an oven at 980° C. for no more than 5 hours; S6, placing the carbon substrate treated in S5 in a composite saponification solution for immersion treatment for at least 12 hours; S7, taking out the carbon matrix after the impregnation treatment and placing it at 250° C.-270° C. for high-temperature curing for no more than 6 hours, and then taking it out of the furnace to obtain a carbon brush body.

10. The method for manufacturing a waterproof carbon brush for a wind turbine according to claim 9, characterized in that: The preparation process of the composite saponified liquid comprises the following steps: Step 1: Aluminum soap and black engine oil in a mass ratio of 10:90 are boiled at 300 degrees Celsius for at least 5 hours to obtain product A, and the product A is white and sticky; Step 2: Add the boiled A into gasoline for dilution to obtain a composite saponified liquid, and the gasoline is No. 95 gasoline, and the mixing ratio of gasoline and product A is 1:1.